Gut microbiota variations over the lifespan and longevity in rabbit’s maternal lines - Iliyass Biada; Maria A. Santacreu; Agustín Blasco; Ramona N. Pena; Noelia Ibáñez-Escriche (Scientific Reports)
Abstract In rabbit breeding, selection for production efficiency traits has been successful but has reduced rabbit functional longevity. The gut microbiota, which influences host health, is linked to longevity and undergoes significant changes with age. While previous studies have focused on young rabbits, research on gut microbiota changes in adult rabbits is limited. Understanding how gut microbiota evolves with age and its impact on longevity of does during reproductive life could offer insights into improving productivity, health and welfare. This study aims to investigate the evolution of gut microbiota through age and to compare different functional longevity groups between and within two maternal rabbit lines with different longevities; a standard commercial line (A) and another founded using longevity criteria (LP). Our analysis demonstrated a significant impact of age on the gut microbiome of does during their reproductive lifespan, with a decline in alpha diversity and change in beta diversity composition as age progressed. Differential abundance analysis revealed that 20% and 16% of taxa in lines A and LP, respectively, were influenced by age, predominantly showing a negative correlation. In terms of functional longevity, differences in abundance between groups were more pronounced within line A, with up to 16% of taxa differing between high-longevity HL (females with more than 10 parities) and low-longevity LL (females died/culled before 5th parity) groups, compared to only 4% within line LP, highlighting the role of genetic background in shaping microbiota composition and its potential influence on longevity. Finally, differences in microbiome between the two lines A and LP were consistent and maintained through their lifespan independently from their longevity. This study reveals that age significantly influences gut microbiome diversity and composition in adult female rabbits, leading to decreased alpha diversity and notable shifts in composition. Microbiome also differs according to functional longevity, with differences varying by genetic line. This suggests that using microbiome through selection or using specific taxa within it as biomarkers could be a promising avenue for improving longevity. Moreover, microbiome differences between genetic lines persist throughout life, even among animals with the same longevity.